2007
DOI: 10.1128/jb.00143-07
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cell Surface-Anchored Cellulose-Binding Protein Encoded by the sca Gene Cluster of Ruminococcus flavefaciens

Abstract: Ruminococcus flavefaciens produces a cellulosomal enzyme complex, based on the structural proteins ScaA, -B, and -C, that was recently shown to attach to the bacterial cell surface via the wall-anchored protein ScaE. ScaA, -B, -C, and -E are all cohesin-bearing proteins encoded by linked genes in the sca cluster. The product of an unknown open reading frame within the sca cluster, herein designated CttA, is similar in sequence at its C terminus to the corresponding region of ScaB, which contains an X module to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 37 publications
2
60
0
Order By: Relevance
“…This modular arrangement represents a common theme shared by XDoc dyads from the CttA and ScaB proteins of both R. flavefaciens strains 17 and FD-1. The dockerin sequences of the latter proteins and their inserts are highly conserved (24). The conserved insertions are unique to the type IIIe dockerins of CttA and ScaB and absent from other known dockerin modules.…”
Section: The Stabilizing Role Of the Dockerin Inserts In The Xdocmentioning
confidence: 99%
See 2 more Smart Citations
“…This modular arrangement represents a common theme shared by XDoc dyads from the CttA and ScaB proteins of both R. flavefaciens strains 17 and FD-1. The dockerin sequences of the latter proteins and their inserts are highly conserved (24). The conserved insertions are unique to the type IIIe dockerins of CttA and ScaB and absent from other known dockerin modules.…”
Section: The Stabilizing Role Of the Dockerin Inserts In The Xdocmentioning
confidence: 99%
“…Gene clustering analysis of several R. flavefaciens strains revealed that the cellulosome system is generally composed of four major scaffoldin subunits, ScaA, ScaB, ScaC, and ScaE, and of a cellulose-binding protein, CttA (19,20). The cohesin, dockerin, and X-modules of these cellulosomal components were found to be divergent in sequence from previously known type I and type II cellulosomal modules, and the Coh-Doc interactions were therefore collectively designated type III on the respective phylogenetic trees (21)(22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ruminococcus spp. are common in ruminants and are frequently found in the hindgut of pigs (42). Adept at degrading cellulose, an increase in Ruminococcus spp.…”
Section: Tetb(p) Tet(q) Tetracyclinementioning
confidence: 99%
“…Spent Avicel with substrate-bound (SB) proteins was isolated by decanting the supernatant (SN) and whole cells (WC) and washing the SB fraction twice with icecold DSMZ medium 640, following which the medium was decanted and combined with the SN-plus-WC fraction. Further washing of the SB fraction was done, as described previously (72), with TBS-Ca-T buffer (25 mM Tris-HCl, pH 7.0, 150 mM NaCl, 1 mM CaCl 2 , and 0.05% [vol/vol] Tween 20). Cell-free SN fraction was obtained by centrifugation at 4°C and 5,000 rpm for 15 min, followed by bottle-top filtration through a 0.22-m-pore-size filter (Millipore).…”
mentioning
confidence: 99%